KEMAMPUAN PEMECAHAN MASALAH MAHASISWA PADA APLIKASI TURUNAN (MAKSIMUM DAN MINIMUM) BERBANTUAN GEOGEBRA - Nurina Kurniasari Rahmawati; Arie Purwa Kusuma; Arfatin Nurrahmah (Delta: Jurnal Ilmiah Pendidikan Matematika, 2023)
Students' problem solving skills are still severely lacking, especially in derivative application materials (maximum and minimum). The purpose of this study is to find out how students' problem solving skills in derivative applications (maximum and minimum) are geogebra-assisted. The method used in this study is qualitative research method, with the focus of the research is the problem solving ability of students in derivative applications (maximum and minimum) assisted by geogebra. The subjects in this study were students of STKIP Kusuma Negara Jakarta who had attended the course or who were following the calculus I course, namely there were 6 students with purposive sampling techniques. The instrument in this study is the researchers themselves, tests to measure problem solving skills and interview guidelines. Data collection techniques are conducted with interviews, obsrevation and documentation. Data analysis techniques performed with data reduction steps, data display, data interpretation, conclusion drawing/verification. Presentation of data The results of the study showed that there is an improvement in student learning outcomes with the existence of mathematical modeling, especially in students with moderate and low problem solving skills, where students have been able to meet four indicators of problem solving, because students still need help in turning problems in problems into mathematical forms. And students with low problem solving skills only meet two problem solving indicators, because students must strive to understand the problems contained in the problem, then need to be directed in order to turn the problem into a form of mathematics